2021
DOI: 10.3390/su13169365
|View full text |Cite
|
Sign up to set email alerts
|

The Drivers-Pressures-State-Impact-Response Model to Structure Cause−Effect Relationships between Agriculture and Aquatic Ecosystems

Abstract: Different segments of society have shown interest in understanding the effects of human activities on ecosystems. To this end, the aim of this article is to analyze the scientific literature on the application of the Drivers-Pressures-State-Impact-Response (DPSIR) conceptual model to identify the parameters used to describe the causal interactions that occur between agriculture and aquatic ecosystems at the watershed scale. In this way, descriptive indicators were established for the data of 63 publications co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 81 publications
0
8
0
Order By: Relevance
“…The DPSIR framework, initially developed by the Organization of Economic Cooperation and Development (OECD) in the late 1980s for ocean ecosystem management, is a framework of a continuous feedback process [ 37 ]. This framework analyses, documents, and reports environmental problems and contains five aspects: "drivers" or the driving forces (D) are commonly recognized as the socioeconomic or cultural factors based on individual or social needs and, in turn, advance to various human activities [ 38 , 39 ].…”
Section: Review Methodologiesmentioning
confidence: 99%
“…The DPSIR framework, initially developed by the Organization of Economic Cooperation and Development (OECD) in the late 1980s for ocean ecosystem management, is a framework of a continuous feedback process [ 37 ]. This framework analyses, documents, and reports environmental problems and contains five aspects: "drivers" or the driving forces (D) are commonly recognized as the socioeconomic or cultural factors based on individual or social needs and, in turn, advance to various human activities [ 38 , 39 ].…”
Section: Review Methodologiesmentioning
confidence: 99%
“…Overall, the frequent literature recommendations to modify DPSIR actually stands as evidence of the flexibility of the original DPSIR framework (Lewison et al, 2016;Pacheco et al, 2007). In a recent review, Troian et al (2021) analysed 63 articles on DPSIR applications in the realm of agriculture and aquatic ecosystems and found that DPSIR was combined with other approaches such as modelling (analytical) and stakeholder engagement (procedural) in 42% of those studies. However, the authors (ibid) noted that stakeholder engagement was, for the most part, vaguely described and therefore likely not well-leveraged.…”
Section: Background To Dpsirmentioning
confidence: 99%
“…Environmental reporting became a routine use for DPSIR, evolving to a conceptual framework for organizing information describing environmental problems via indicators and statistics, and their relationship to the socio-economic domain to support policy development and decision-making (Cooper, 2013;Svarstad et al, 2008). DPSIR is more often utilized European contexts, with Asian, African, American and Oceanic applications appearing less frequently in the literature (Troian et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Responses targeted further upstream of this causal pathway are considered to have the strongest impact (Figure ). DPSIR provides a single framework for integrating social, cultural, and economic aspects of an issue and has been shown to allow the visualization of interactions within systems, identification of research gaps and intervention strategies, organization of information, and development of computational models …”
Section: Introductionmentioning
confidence: 99%
“…DPSIR provides a single framework for integrating social, cultural, and economic aspects of an issue and has been shown to allow the visualization of interactions within systems, identification of research gaps and intervention strategies, organization of information, and development of computational models. 13 In this study, we explored whether the DPSIR framework could be applied to AMR in a complex food-producing environment case study, namely, that of a rural aquaculture environment in north-central Bangladesh, in order to understand and delineate the connectivity between AMR and wider sustainable development issues. Aquaculture is the fastest growing food sector globally, with industry expansion largely being facilitated through the rapid intensification of existing aquaculture farms in LMICs in Asia.…”
Section: ■ Introductionmentioning
confidence: 99%